ACUTE MYOCARDITIS FOLLOWING COVID-19 VACCINATION: A PECULIAR CASE SERIES. (June 2022) - Corradetti, Sara; Sclafani, Matteo; Mistrulli, Raffaella; Gallo, Giovanna; Pagannone, Erika; Di Girolamo, Marco; Autore, Camillo; Volpe, Massimo; Battistoni, Allegra
Abstract : Objective: Although acute myocarditis has not been observed as an adverse event in landmark trials of COVID-19 vaccines, it has been reported as a rare complication in real-world. The study aims to report a single-center experience on this issue. Design and method: We identified five cases of acute myocarditis with consistent temporal association to administration of COVID-19 vaccine and described clinical, serological, echocardiographic and cardiac magnetic resonance findings both in the acute phase and after a median follow up of 6 months. Results: All five patients received a COVID-19 vaccination dose within 24 to 96 hours before the onset of symptoms. Four patients received an mRNA vaccine (Comirnaty or Spikevax) and one received the adenovirus vaccine (Janssen). Only one patient had a known prior COVID-19 infection. All patients presented with chest pain and troponin I elevation occurring after the first vaccine dose in four cases. All patients tested negative for acute COVID-19 infection by polymerase chain reaction at admission. Blood tests revealed no or only mild inflammatory serological changes. Only one patient developed an increase in white blood cell count. None had specific changes on electrocardiography and echocardiography demonstrated preserved left ventricular systolic function and no regional wall motion abnormalities in all patients. Three patients underwent coronary angiography since risk factors and troponin trends raised clinical suspicion of acute coronary syndrome, none showed evidence of obstructive coronary artery disease. All patients had a mild to moderate disease not complicated by acute heart failure or arrhythmias. Cardiac Magnetic Resonance was performed in four cases and showed myocardial oedema and late gadolinium enhancement during the acute phase with persistence of areas of late gadolinium enhancement after a median follow-up of 6 months. None had further symptoms or hospitalizations since discharge. Conclusions: Acute myocarditis following COVID-19 vaccination is a well-defined clinical entity. Our findings suggest an immune rather than inflammatory pathogenesis and a benign course without clinical complication after a median follow-up of 6 months, but further studies are needed to define the prognostic significance of persistent findings on cardiac magnetic resonance.